The effort of counseling guidance teacher in developing student learning motivation - Fahrurrazi Fahrurrazi; Riska Damayanti (Journal of Advanced Guidance and Counseling, 2021)
Purpose -  This study aims to find out the efforts of guidance and counseling Madrasah Aliyah (MA) Madania teachers in developing students' learning motivation.  Method - This study uses a qualitative approach descriptive. The subjects of this study amounted to 6 people, namely 1 guidance and counseling teacher (BK), and 5 students of MA Madania. The data-collection technique in this study uses observations and interviews.Result - The results showed that the students who had done guidance and counseling realized that learning was important and had undergone changes. The changes were like before, they did not want to learn, when they were asked to study they avoided it, they also did not want to do assignments, and slept when the teacher was explaining and so on. When given counseling guidance, there are changes in which they start to have an effort in learning such as: willing to do assignments, study independently and study in groups with friends.Implications – The results of this study are expected to be input in improving several things that need to be done by counseling guidance teachers in schools.Originality - Motivational improvement framework with the efforts of BK MA Madania teachers in developing student learning motivation.***Tujuan - Penelitian ini bertujuan untuk mengetahui upaya guru bimbingan dan konseling Madrasah Aliyah (MA) Madania dalam mengembangkan motivasi belajar siswa.Metode - Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subyek penelitian ini berjumlah 6 orang yaitu 1 orang guru bimbingan dan konseling (BK), dan 5 orang siswa MA Madania. Teknik pengumpulan data dalam penelitian ini menggunakan observasi dan wawancara.Hasil - Hasil penelitian menunjukkan bahwa siswa yang telah melakukan bimbingan dan konseling menyadari bahwa belajar itu penting dan telah mengalami perubahan. Perubahannya seperti dulu, mereka tidak mau belajar, ketika diminta untuk belajar mereka menghindarinya, mereka juga tidak mau mengerjakan tugas, dan tidur ketika guru sedang menjelaskan dan sebagainya. Ketika diberikan bimbingan konseling, terjadi perubahan dimana mereka mulai memiliki usaha dalam belajar seperti: mau mengerjakan tugas, belajar mandiri dan belajar berkelompok dengan teman.Implikasi - Hasil penelitian ini diharapkan menjadi input dalam meningkatkan beberapa hal yang perlu dilakukan oleh guru bimbingan konseling di sekolah.Originalitas - Kerangka peningkatan motivasi dengan upaya guru BK MA Madania dalam mengembangkan motivasi belajar siswa.